2006
DOI: 10.1227/01.neu.0000193518.71825.d7
|View full text |Cite
|
Sign up to set email alerts
|

DuraSeal Magnetic Resonance and Computed Tomography Imaging: Evaluation in a Canine Craniotomy Model

Abstract: The hydrogel sealant can be observed with cross sectional imaging and can be distinguished from cerebrospinal fluid using a CT scan, complemented by an occasional MRI scan. In addition, complete absorption of the hydrogel, with closure of the remaining void was noted. Histological examination found an unremarkable response with no neurotoxicity or space-filling defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…However, one of the drawbacks of using DuraSeal TM is its potential to swell up to 50% and its slow resorption rate. The peak expansion of DuraSeal TM was between 3 and 14 days postapplication in a dog model with complete resorption at 8 weeks [6,10]. Owing to these findings, we believe the application of DuraSeal TM in a confined bony area is contraindicated as a result of the concern of swelling and nerve root compression (DuraSeal TM product information.…”
Section: Discussionmentioning
confidence: 95%
“…However, one of the drawbacks of using DuraSeal TM is its potential to swell up to 50% and its slow resorption rate. The peak expansion of DuraSeal TM was between 3 and 14 days postapplication in a dog model with complete resorption at 8 weeks [6,10]. Owing to these findings, we believe the application of DuraSeal TM in a confined bony area is contraindicated as a result of the concern of swelling and nerve root compression (DuraSeal TM product information.…”
Section: Discussionmentioning
confidence: 95%
“…8 Both fibrin glue and PEGH have a high water content and thus have characteristics similar to CSF or reactive inflammation on MR imaging. 9 Furthermore, they are applied over the dural repair, exactly where a postoperative CSF collection or infection may be expected to form. In patients treated with fibrin glue or PEGH, MR images obtained within the first few weeks of surgery to assess postoperative pseudomeningocele are difficult to interpret.…”
mentioning
confidence: 99%
“…One study has examined the radiographic appearance of PEGH in a canine model 9 ; however, to our knowledge, there is no existing comparison of MR imaging appearance in patients in the immediate postoperative timeframe. The analysis will seek to describe the signal characteristics of these 3 sealants under MR imaging and to establish criteria for distinguishing appropriately placed dural sealants from pseudomeningocele.…”
mentioning
confidence: 99%
“…8,9 In a dog model, DuraSeal's volume expansion was reported to peak between day 3 and 2 weeks after implantation. 10 No quantification of volume expansion is made after application of a 3-mm layer on the intracranial dural surface, but cortical displacement due to the mass effect is noted. Complete absorption of the hydrogel was noted by week 10.…”
Section: Discussionmentioning
confidence: 99%
“…Complete absorption of the hydrogel was noted by week 10. 10 In human intracranial use of DuraSeal, Cosgrove et al reported 75.4% reduction in the thickness of the sealant by 3 months. 11 Blackburn reports a case of cervicomedullary compression after the use of DuraSeal in the repair of the dura overlying the posterior fossa.…”
Section: Discussionmentioning
confidence: 99%